The Influence of Information Technology on Mining Conflicts in East Kalimantan - Pamuncak, Aristya Windiana; Mubarok, Asnawi (Universitas Muhammadiyah Surakarta, 2024)
Although IT improves operational efficiency and safety, information technology also brings new problems and needs to fully address the legal and environmental issues associated with mining. By facilitating communication, disseminating information, and providing a platform for mediation and dispute resolution, information technology (IT) is very helpful in resolving conflicts in East Kalimantan. Information technology significantly impacts conflict resolution in mining by improving communication, facilitating data analysis, and providing better decision-making tools. However, the use of IT in mining is not free from risks. This research adopts a descriptive-analytical method, combining literature reviews and relevant experts' opinions. Moreover, this paper uses normative juridical research methods to discuss how information technology influences mining conflicts in East Kalimantan. The discussion results conclude that Information Technology (IT) integration in the mining industry has had significant positive and negative impacts. It is essential to achieve sustainable development in mining by increasing productivity, safety and environmental efficiency. However, IT adoption in mining also presents challenges. The overall impact of IT in mining is very significant. To ensure technological sovereignty, it offers a safer, more efficient, and more sustainable future for the ongoing digital transformation industry, including domestic software development. The results of this discussion show how crucial IT is to maintain industrial stability and overcome the problem of technological fragmentation and the need for solutions. Teknologi informasi (TI) membantu efisiensi dan keselamatan operasi, namun juga memunculkan kekhawatiran dan kebutuhan baru untuk mengatasi masalah hukum dan lingkungan pertambangan. TI berkontribusi pada penyelesaian konflik di Kalimantan Timur dengan meningkatkan komunikasi, menyebarkan informasi, dan menawarkan tempat untuk mediasi dan penyelesaian sengketa. Kemampuan komunikasi, analisis data, dan pengambilan keputusan yang ditingkatkan oleh teknologi informasi sangat berpengaruh terhadap penyelesaian sengketa pertambangan. Namun, serangan siber dapat mengganggu sistem, menyebabkan waktu henti yang merugikan, masalah keamanan, dan pencurian data di pertambangan. Studi deskriptif-analitis ini menggunakan tinjauan literatur dan pendapat para ahli. Tulisan ini juga membahas bagaimana teknologi informasi mempengaruhi konflik pertambangan di Kalimantan Timur dengan menggunakan pendekatan penelitian yuridis normatif. Hasil pembahasan menunjukkan bahwa integrasi TI di pertambangan telah memberikan dampak positif dan negatif. Peningkatan produksi, keselamatan, dan efisiensi lingkungan diperlukan untuk pembangunan pertambangan yang berkelanjutan. Adopsi TI di pertambangan juga memiliki tantangan yang sama. TI memiliki dampak besar pada pertambangan. TI memberikan masa depan yang lebih aman, lebih efisien, dan lebih berkelanjutan untuk transformasi digital, termasuk pengembangan perangkat lunak dalam negeri, untuk memastikan kedaulatan teknis. Studi ini menunjukkan betapa pentingnya TI untuk stabilitas industri, fragmentasi teknis, dan solusi.